Refuting New Atheism: A Critical Response to Richard Dawkins and Its Negative Impacts on Korean Society with Proposed Solutions - Ayman Turk; Amal Fathullah Zarkasyi; M. Kholid Muslih (University of Darussalam Gontor, Indonesia, 2025)
This article critically examines the ideology of New Atheism, with particular focus on the writings and influence of Richard Dawkins. New Atheism, which rose to prominence in the West after the events of September 11, 2001, challenges religious belief through aggressive rationalism and popular science. Richard Dawkins, a key figure, is best known for The God Delusion, which has sparked wide global debate. This study explores the impact of New Atheism on Korean society, highlighting its moral and social implications, including the normalization of incest, bestiality, child exploitation, and abortion. Methodologically, this study applies inductive, critical-analytical, historical, and statistical approaches to refute atheistic claims and to promote Islamic theological responses. The research addresses four central questions: the origins and spread of New Atheism, the arguments used by its proponents, the rational proofs for the existence of God, and effective strategies to mitigate its influence. The study concludes that collaborative efforts among scholars, institutions, and society are vital in countering the spread of atheism and guiding youth toward faith and moral clarity.